ANALISIS SKALA EKONOMI PADA USAHA TANI SALAK DI DESA SIBETAN, KECAMATAN BEBANDEM, KABUPATEN KARANGASEM - Dewi, Ni Made Diah Kusuma; Utama, Made Suyana (E-Jurnal Ekonomi Pembangunan Universitas Udayana; Vol 10 No 10 (2021): VOL 10 NO 10, OKTOBER 2021 [3966 - 4405], 2021)
One of the famous local agricultural products in Sibetan , Bebandem , Karangasem is zalacca. The purpose of this study is to analyze the economies of scale in salak farming in Sibetan , Bebandem , Karangasem . This study uses 144 salak farmers, 76 farmers from farmers group and 68 farmers from non farmers group as samples. Data areanalyzed by regression analysis in the form of Cobb-Douglas production function. The results showes that simultaneously capital, labor, and land area has  positive and significant effect on the production of salak. Partially capital, labor, and land area have a positive and significant effect on the production. The economies of scale in the salak farming business in Sibeta n , Bebandem, Karangasem are in a condition of increasing return to scale. keyword : production, capital, labor, land area.